FTIR Characterization of Asphalt SARA Fractions in Response to Rubber Modification - Mohyeldin Ragab; Eslam Deef-Allah; Magdy Abdelrahman (Applied Sciences)
Asphalt–rubber binders (A-RBs) have a long and deep history of use; however, little is known regarding the interrelated chemical behaviors and miscibility of rubber with the asphalt fractions [saturates, aromatics, resins, and asphaltenes (SARA)]. This study comprehensively attempted to address this knowledge deficiency by employing Fourier transform infrared spectroscopy (FTIR) to investigate the chemical evolution of A-RBs. A-RB interacted at 190 °C and 3000 min−1 for 8 h was deemed to have the optimal rheological performance. FTIR of the liquid fractions of A-RB 190–3000 showed a prominent chemical shift in the SARA fractions, with new peaks that showed rubber polybutadiene (PB) and polystyrene migration into asphaltenes. Meanwhile, decreases in peaks with C–H aromatic bending and S=O stretching for the A-RB 190–3000 saturates showed that the rubber absorbed low-molecular-weight maltenes during swelling. Peaks associated with C=C aromatic appeared in saturates and aromatics, respectively, emphasizing that unsaturated components migrated from the rubber into the asphalt. Thermal analysis showed that rubber dissolution for this sample reached 82%. While a PB peak existed in asphaltenes of A-RB 220–3000, its intensity was diminished by depolymerization, thus compromising the integrity of the migrated rubber structure and generating less rheological enhancement. This study concludes that FTIR characterization of SARA fractions offers valuable insights into the interactions between asphalt and rubber, and that regulated processing conditions are essential for enhancing binder performance.